172P miR-486-5p counteracts the shedding of MICA/B and CD155 immune-ligands in TNBC patients. (15th December 2019) - Elkhouly, A; Youness, R A; Gad, M
Abstract: Background: Triple Negative Breast Cancer (TNBC) is the most belligerent subtype of BC. Yet, it is considered the best candidate for immunotherapy. As TNBC microenvironment is rich in CD8+ T lymphocytes (CTLs) and Natural Killer cells (NKs), the main key players in BC immune surveillance. During the antitumor immune-response, CTLs and NKs recognize and eliminate BC cells through an array of activating receptors expressed on their surface. CD226 and NKG2D are among the most vital activating receptors present on CTLs, NKs and NKT cells. The rate limiting step in tumor eradication is the binding of the aforementioned receptors to their respective ligands (Major histocompatibility complex class I chain-related proteins A and B (MICA/B) and CD155). Unfortunately, recent studies highlight the extensive shedding of MICA/B and CD155 in TNBC patients. Lately, our group nominated miR-486-5p as an immuno-activating miRNA. However, its impact on TNBC immune ligands has never been investigated. Therefore, our aim is to investigate the impact of miR-486-5p on MICA/B and CD155 in an attempt to alleviate the immune-suppressive nature of TNBC cells. Methods: TNBC patients (n = 25) were recruited. Bioinformatics were performed to verify the binding of miR-486-5p to MICA/B and CD155. MDA-MB-231 and MCF7 cells were cultured and transfected with miR-486-5p oligonucleotides. Total RNA was extracted and quantified by qRT-PCR. Cellular viability and clonogenicity were performed using MTT and colony forming assays, respectively. Results: TNBC patients showed a significant down-regulatory pattern of miR-486-5p, MICA, MICB and CD155 compared to its normal counterparts. In a similar pattern, miR-486-5p, MICA, MICB and CD155 were found to be markedly down-regulated in MDA-MB-231 cells. In-silico results proved that miR-486-5p potentially targets MICA, MICB and CD155. Ectopic expression of miR-486-5p (>1000 folds) resulted in a marked induction of MICA/B (2 folds) and CD155 (5 folds) thus potentiating NKs and CTLs cytotoxicity. Functionally, miR-486-5p mimics resulted in a significant repression of TNBC cellular viability and colony forming ability. Conclusion: miR-486-5p is an immunomodulatory tumor suppressor miRNA acts by alleviating the immunesuppressive profile of TNBC cells. Legal entity responsible for the study: German University in Cairo. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.